In search of a queer pathos: Connections between Aby Warburg and Queer Studies - Dieison Marconi; Gabriela Machado Ramos de Almeida (Acta Poética)
The paper investigates connections between queer studies and the contributions of Aby Warburg to image theories, specifically the notion of time as a fundamental conceptual operator in the work of Warburg and his main exegete, Georges Didi-Huberman, from whom we sought help in the endeavor of envisioning a queer pathos that would survive in visual culture. Time is also at the core of a certain criticism by some authors of queer studies to the notion of chrononormativity as biopolitical regulation. This paper attempts to understand how Warburgian notions of Nachleben and Pathosformel help to investigate how abject and anachronistic gestures which keep reappearing as a queer symptom in culture, disorganizing a “natural model” of history of art and breaking with the history of progress that organizes relations between gender, body and sexuality according to disciplinary temporal schema.